Informal institutions, transaction risk, and firm productivity in Myanmar - Michael Danquah; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In many low-income transition countries, where formal institutions such as courts do not function effectively, informal institutions are often used by firms to minimize transaction risks. We examine the role of informal institutions, in the forms of relational contracting and social networks, in determining the risks that firms are willing to bear in their transactions with their suppliers and customers, and whether firms that bear such risks have higher firm productivity. Our country context is Myanmar, a country which is making a transition from a socialist to marketoriented economy. Using an unique dataset of 2,496 micro, small, and medium firms, we find that firms that engage in risk taking are significantly more productive than firms that do not, and such firms are more likely to utilize informal institutions, such as acquiring information from informal interaction with customers, and social networks, including information received from business networks by firms, talking to other suppliers of customers, and being a member of a business association. Our findings suggest that informal institutions can be effective substitutes for formal institutions that are often absent or not effective in low-income transition economies.
Keywords: O12; O43; P26; 330; firm productivity; informal institutions; Myanmar; relational contracting; socialnetworks; transition economies